Urban planning risks of losing cultural heritage - Elena V. Scherbina; Ali Salmo (Stroitel’stvo: Nauka i Obrazovanie, 2022)
Introduction. Cultural heritage: monuments, ensembles, buildings and structures, archaeological sites define the urban identity of a settlement, reflect the historical development path of the people and are one of the main priorities in urban development. Urban risks are considered as the possibility of something happening that has a negative impact on the sites, as well as any possible loss that affects the value of cultural heritage, which can be divided into several categories.Materials and methods. From the point of view of the Sets Theory, the description of changes in the totality of tangible and intangible cultural heritage, occurring as a result of natural and anthropogenic factors, which allows to determine the main risks of its loss, has been proposed. The suggested mathematical model serves as the basis for the development of information tools for identification, assessment and consideration of historical and cultural heritage in urban planning.Results. Based on a retrospective analysis of the historical development of Homs, a classification of cultural heritage sites has been proposed, and a diagram of the transformation of the collectivity of objects of tangible and intangible cultural heritage as a result of natural and human factors of the risk of their loss has been created.Conclusions. It was found that the highest risks of loss of immovable objects of cultural heritage include natural catastrophic processes and phenomena (earthquakes), and military conflicts. As a result of which, in particular in the city of Homs, a new local architectural style “Homsi” was formed to replace the Byzantine culture.